Lollipop-induced oral lichenoid reaction in a child - Bastos, Daniela B. [UNESP]; Santos, Ingrid S. [UNESP]; Valente, Vitor B. [UNESP]; Biel, Antônio Carlos O.; Felipini, Renata C. [UNESP]; Biasoli, Eder R. [UNESP]; Miyahara, Glauco I. [UNESP]; Bernabé, Daniel G. [UNESP] (Wiley, 2016)
Background: Oral lichenoid reactions (OLRs) have been rarely reported in pediatric patients. Case Report: This article reports an unusual case of a 15-year-old girl who had white plaques in tongue and buccal mucosa oral which initially were diagnosed as oral lichen planus (OLP). At first, the patient and her family denied systemic or local medication use. Biopsy was performed, and histopathological aspects were suggestive of OLP. Despite the attempt of treatment with topical corticoid, the lesions did not recede. Patient's behavior and medical history were again investigated and revealed that she had been using almost daily in her school an artificially colored and flavored lollipop. One week after removing lollipop use behavior, the oral lesions showed complete resolution and OLR diagnosis was defined. Conclusion: The present case denotes that OLR should be considered in the differential diagnosis of oral white plates in children and artificially colored sweets can be its causal agent.